2023
DOI: 10.1523/jneurosci.1657-22.2023
|View full text |Cite
|
Sign up to set email alerts
|

Neural Ensemble Fragmentation in the AnesthetizedDrosophilaBrain

Abstract: General anesthetics cause a profound loss of behavioral responsiveness in all animals. In mammals, general anesthesia is induced in part by the potentiation of endogenous sleep-promoting circuits, although ‘deep’ anesthesia is understood to be more similar to coma (Brown et al., 2011). Surgically relevant concentrations of anesthetics such as isoflurane and propofol have been shown to impair neural connectivity across the mammalian brain (Mashour and Hudetz, 2017; Yang et al., 2021), which presents one explana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 71 publications
1
8
0
Order By: Relevance
“…We found that there is significantly more overlap between successive 5min sleep epochs (41%), compared to the waking average ( Figure 5G ), suggesting less neural turnover during THIP-induced sleep than during wake. This contrasts with optogenetic sleep, where the rate of neural turnover was not different from wake [36]. Taken together, our calcium imaging data confirm that pharmacological sleep induction promotes a different kind of sleep than optogenetic sleep induction in the same strain.…”
Section: Thip-induced Sleep Decreases Brain Activity and Connectivitysupporting
confidence: 53%
See 3 more Smart Citations
“…We found that there is significantly more overlap between successive 5min sleep epochs (41%), compared to the waking average ( Figure 5G ), suggesting less neural turnover during THIP-induced sleep than during wake. This contrasts with optogenetic sleep, where the rate of neural turnover was not different from wake [36]. Taken together, our calcium imaging data confirm that pharmacological sleep induction promotes a different kind of sleep than optogenetic sleep induction in the same strain.…”
Section: Thip-induced Sleep Decreases Brain Activity and Connectivitysupporting
confidence: 53%
“…This confirmed that the brief exposure to THIP was indeed putting flies to sleep, with an expected sleep inertia lasting the length of a typical spontaneous sleep bout [15, 16]. This contrasts with optogenetic sleep induction using the R23E10-Gal4 circuit, which does not show appear to show any sleep inertia ( Figure 4C ) [36].…”
Section: Thip-induced Sleep Decreases Brain Activity and Connectivitymentioning
confidence: 54%
See 2 more Smart Citations
“…Our multichannel data add to the growing realization that the entire insect brain engages in dynamical patterns of activity during both sleep and wake (17,43) and does not simply shut off when insects become immobile or quiescent. To understand these patterns of activity and how they might relate to conserved sleep functions (50) requires agnostic approaches derived from (for example) machine learning, as done in this study, rather than approximations inspired from human EEG.…”
Section: Discussionmentioning
confidence: 80%